Transcriptomic and Lipidomic Analysis of Lipids in Forsythia suspensa - Wu, Bei; Li, Yinping; Zhao, Wenjia; Meng, Zhiqiang; Ji, Wen; Wang, Chen (Frontiers in Genetics, 2021)
Forsythiae Fructus (Lianqiao in Chinese) is widely used in traditional Chinese medicine. The lipid components in Forsythiae Fructus are the basis of plant growth and active metabolism. Samples were collected at two growth stages for a comprehensive study. Transcriptome and lipidomics were performed by using the RNA-seq and UPLC-Q-TOF-MS techniques separately. For the first time, it was reported that there were 5802 lipid components in Lianqiao comprised of 31.7% glycerolipids, 16.57% phospholipids, 13.18% sphingolipids, and 10.54% fatty acids. Lipid components such as terpenes and flavonoids have pharmacological activity, but their content was low. Among these lipids which were isolated from Forsythiae Fructus, 139 showed significant differences from the May and July harvest periods. The lipids of natural products are mainly concentrated in pregnenolones and polyvinyl lipids. RNA-Seq analysis revealed 92,294 unigenes, and 1533 of these were differentially expressed. There were 551 differential genes enriched in 119 KEGG pathways. The de novo synthesis pathways of terpenoids and flavonoids were explored. Combined with the results of lipidomics and transcriptomics, it is hypothesized that in the synthesis of abscisic acid, a terpenoid, may be under the dynamic regulation of genes EC: 1.1.1.288, EC: 1.14.14.137 and EC: 1.13.11.51 in balanced state. In the synthesis of gibberellin, GA20-oxidase (GA20ox, EC: 1.14.11.12), and GA3-oxidase (GA3ox, EC: 1.14.11.15) catalyze the production of active GAs, and EC: 1.14.11.13 is the metabolic enzymes of active GAs. In the synthesis of flavonoids, MF (multifunctional), PAL (phenylalanine ammonia-lyase), CHS (chalcone synthase), ANS (anthocyanidin synthase), FLS (flavonol synthase) are all key enzymes. The results of the present study provide valuable reference information for further research on the metabolic pathways of the secondary metabolites of Forsythia suspensa.